PHILOSOPHY OF CULTURE M.M. BAKHTIN: HISTORICAL AND ANTHROPOLOGICAL DIMENSION - Spartak Sh. Aytov (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
The purpose of this paper is to determine the influence of theoretical approaches to the philosophical concepts of culture M. M. Bakhtin on the genesis and implementation of historical and anthropological concepts and renovations mentality and socio-cultural characteristics and behavior of individuals and societies of the past. Methodology. Methodological tools are methods of system and source analyses. Theoretical basis and results: analyzes the concept of the philosophy of culture such M.M. Bakhtin as a carnival, folk culture, culture of humor, doubleworld, concept social-cultural projection material and cultural bottom and its impact on the culture of laughter European Middle Ages and Renaissance. Methodological approaches Bakhtin recreated for historical and anthropological reconstruction mentality and socio-cultural realities of the high Middle Ages and the Renaissance. Investigated the perception of philosophical and cultural concepts M. M. Bakhtin, the scientific community and their impact on the historical and anthropological studies. It was also analyzed the influence of the respective ideas M.M. Bakhtin's historical and anthropological studies of the last quarter of XX - beginning of XXI century. in particular on the work of D. Likhachev, A. Gurevich, E. Thompson and other researchers. Conclusion: concept of the philosophy of culture, MM Bakhtin, in particular, the culture of humor, the popular perception of the world, carnival, social and cultural doubleworld, reconstruction of the domestic foundations of culture laughter Europe era high Middle Ages and the Renaissance were one of the most important conceptual elements in the study of the mentality of socially significant behavior and daily life as these periods, so or any other, from the early Middle Ages to the present.